The Mediator Role of Organizational Justice in the Relationship Between School Principals’ Agile Leadership Characteristics and Teachers’ Job Satisfaction - Özgenel, Mustafa; Yazıcı, Şebnem; Asmaz, Adem (Frontiers in Psychology, 2022)
Teachers with high job satisfaction become more effective and productive by showing high performance and positively affecting student and school outcomes. This study investigates the relationship between school principals’ agile leadership characteristics, organizational justice, and job satisfaction, and sheds light on the role of organizational justice in the relationship between agile leadership and job satisfaction. To achieve this aim, a theoretical model has been put forward and this model has been tested with the data collected from 409 teachers working in public schools in Istanbul. The results show that school principals with high agile leadership characteristics and organizational justice are associated with teachers’ job satisfaction. The analyses also indicate that organizational justice strongly contributes to the relationship between agile leadership and job satisfaction and plays an important role in the relationship between the two determinants.